EKSPRESI SIMBOLIK OEN RANUP PADA KARYA INTERIOR RUANG TAMU - Zahratun Nisa (Institut Seni Indonesia Padangpanjang, 2023)
Oen Ranup is the name for betel leaf by the people of Aceh. It consists of two syllables, namely Oen which means leaf and Ranup which means betel. The artist’s interest in taking Oen Ranup as the idea of creating textile art is that it is because unique in terms of a shape that resembles a heart shape and a green color that gives a fresh impression. This Oen Ranup has been used since the royal era until now, it is still brought into the series of Acehnese customs, making the craftsmen interested in expressing Oen Ranup into the interior of the living room. The method used in this work goes through several stages,the first stage is the pre-design stage, namely the imagination development step. The second stage of design is to realize visual ideas by making alternative designs, the third stage is embodiment, namely alternative sketches that have been selected will be realized into a work. Furthermore,the presentation is an exhibition with the aim of establishing communication between artists and art connoisseurs through exhibitions. The concept used in making this work using the concept of symbolic expression is a modern art form by utilizing traditional idioms as a basic part of its composition. In the creation of this final project, the artist applies Oen Ranup to the interior of the living room with embroidery techniques. The works are Sofa Pillows, wall clocks.